Old texts, new practices Islamic reform in modern Morocco - Terem, Etty 1967- (Stanford University Press, 2014)
In 1910, al-Mahdi al-Wazzani, a prominent Moroccan Islamic scholar completed his massive compilation of Maliki fatwas. An eleven-volume set, it is the most extensive collection of fatwas written and published in the Arab Middle East during the late nineteenth and early twentieth centuries. Al-Wazzani's legal opinions addressed practical concerns and questions: What are the ethical and legal duties of Muslims residing under European rule? Is emigration from non-Muslim territory an absolute duty? Is it ethical for Muslim merchants to travel to Europe? Is it legal to consume European-manufactured